Implication of Right Issue Cum and Ex-Date Announcement to the Stock Return(Empirical Study on Indonesia Stock Exchange Period: 2009-2012) - Sugiana, Bilfian; Surya, Budhi Arta (The Indonesian Journal of Business Administration, 2013)
Rights issue is one of corporate actions conducted by the company in order to increase the new funds through issuance of new shares. The common purposes from issuing right issue are to improve company’s capital structure in pursuance of expanding their business as well as meet the need for a new stream of funds in terms of the debt repayment. Therefore, right issue is a signal that may be good or bad news for investor’s investment decision depending on the company’s objectives. This study aimed to test market efficiency by analyzing the right issue cum and ex-date event in Indonesia Stock Exchange. The object of this research is the content of information by observing changes in stock prices and return around observation period. To examine the object, the populations used in this study are all publicly traded companies in the Indonesian Stock Exchange (IDX) which are performed corporate action in right issue during 2009-2012 periods. The period consisting 74 events of right issues captured in the 30-days of observation. Scopes of the research covers the analysis using the event study conducted to capture market reaction reflected by the changes of abnormal return. The estimation used to test information content which implicated to the stocks return by the events in order to test the semistrong form of market efficiency using form of public information available as an object of study and selecting performance of stock that generates the best return during the event using Jensen’s Rules analysis. In the further analysis of the market reaction, company is divided into two categories which are growing and not growing companies conducted by proxy investment opportunity set (IOS) MVE/BVE. From the analysis shows that the market reacted negatively before and after the event both for growing and not growing companies by its significant abnormal return.  Keywords: Right issue, Ex-date event, Abnormal Return, Event Study, Market Efficiency, Investment Opportunity Set (IOS) MVE/BVE, Jensen’s Rule.